Saccharomyces eubayanus and Saccharomyces uvarum associated with the fermentation of Araucaria araucana seeds in Patagonia - Rodríguez, María Eugenia (2014)
Mudai is a traditional fermented beverage, made from the seeds of the Araucaria araucana tree by Mapuche communities. The main goal of the present study was to identify and characterize the yeast microbiota responsible of Mudai fermentation as well as from A. araucana seeds and bark from different locations in Northern Patagonia. Only Hanseniaspora uvarum and a commercial bakery strain of Saccharomyces cerevisiae were isolated from Mudai and all Saccharomyces isolates recovered from A. araucana seed and bark samples belonged to the cryotolerant species Saccharomyces eubayanus and Saccharomyces uvarum. These two species were already reported in Nothofagus trees from Patagonia; however, this is the first time that they were isolated from A. araucana, which extends their ecological distribution. The presence of these species in A. araucana seeds and bark samples, led us to postulate a potential role for them as the original yeasts responsible for the elaboration of Mudai before the introduction of commercial S. cerevisiae cultures. The molecular and genetic characterization of the S. uvarum and S. eubayanus isolates and their comparison with European S. uvarum strains and S. eubayanus hybrids (S. bayanus and S. pastorianus), allowed their ecology and evolution us to be examined.